Community Pharmacy–Based Inducement Programs Associated With Better Medication Adherence: A Cohort Study. (August 2017) - Simpson, Scot H.; Lin, Mu; Eurich, Dean T.
Background: Inducement programs can promote customer loyalty; however, the clinical effects of these programs are unknown.Objective: To examine relationships among inducement program use, medication adherence, and health outcomes.Methods: Alberta residents with ≥ 1 physician visit for diabetes or hypertension between April 2008 and March 2014 were eligible for this study and included if they were new statin users and alive at least 455 days after the first statin dispensation. Group assignment was based on whether all statin dispensations in the first year were obtained from pharmacies with or without inducement programs. Discontinuation was defined as no statin dispensations between 275 and 455 days after the first statin dispensation. Acute coronary syndrome (ACS) hospitalizations or deaths were identified between 456 days and 3 years after the first statin dispensation. Multivariable regression analyses were conducted to examine relationships among inducement program use, discontinuation, and ACS events.Results: Among the 159 998 new statin users, mean age was 60.2 (±13.7) years and 67 534 (42%) were women. Statin discontinuation occurred in 22 455 (28.9%) of 77 803 inducement group participants and 25 816 (31.4%) of 82 195 noninducement group participants (adjusted odds ratio = 0.88; 95% CI = 0.86-0.90). Risk of an ACS event was similar between groups (adjusted hazard ratio = 1.00; 95% CI 0.92-1.08); however, discontinuing statin therapy was associated with a higher risk of an ACS event (adjusted hazard ratio = 1.27; 95% CI = 1.16-1.39).Conclusions: Inducement programs are associated with better adherence and not directly associated with risk of health outcomes.